1986
DOI: 10.1021/jo00354a001
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed decarboxylative allylic alkylation of allylic acetates with .beta.-keto acids

Abstract: In the presence of a catalytic amount of tetrakis(triphenylphosphine)palladium, /3-keto acids react with allylic acetates at ambient temperature to produce -allylic ketones in good yields with quantitative decarboxylation. This palladium-catalyzed decarboxylative allylic alkylation of allylic acetates with /3-keto acids is characterized by high regio-and stereoselectivity. Allylation of /3-keto acid takes place at the carbon atom bearing a carboxyl group. Allylic alkylation of allylic acetate with /3-keto acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…However, Saegusa has shown that the acylation step is not necessary when β-keto acids are utilized as reactants. 26 Specifically, he demonstrated the intermolecular coupling of allyl acetates and β-keto acids or β-keto carboxylates (Table 1). The largest limitation to this reaction appears to be the requirement of a substrate β-ketoacid that bears an α-proton; we will return to this subject in the discussion of the mechanisms of decarboxylative allylation.…”
Section: Decarboxylative Allylation Of Enolatesmentioning
confidence: 99%
“…However, Saegusa has shown that the acylation step is not necessary when β-keto acids are utilized as reactants. 26 Specifically, he demonstrated the intermolecular coupling of allyl acetates and β-keto acids or β-keto carboxylates (Table 1). The largest limitation to this reaction appears to be the requirement of a substrate β-ketoacid that bears an α-proton; we will return to this subject in the discussion of the mechanisms of decarboxylative allylation.…”
Section: Decarboxylative Allylation Of Enolatesmentioning
confidence: 99%
“…[30] The decarboxylative substitution is facile, occurring at room temperature in either benzene or THF. [30] The decarboxylative substitution is facile, occurring at room temperature in either benzene or THF.…”
Section: Allylation Of β-Keto Acidsmentioning
confidence: 99%
“…They were known: R = allyl: 8a, 23 8b, 27 9a, 24 9b. 28 (20) The reaction of 2-methylcyclohexanone potassium enolates prepared from ketone 1b (tBuOK (1 eq. ), THF, -20°C, 1h) with benzyl bromide (THF, -78°C, 1h) yielded ketone 8b (R = benzyl) with a 38% chromatographed yield.…”
Section: General Procedures For Alkylation Of Lithium Enolates 5 Andmentioning
confidence: 99%